PIK3CA and KRAS Amplification in Esophageal Adenocarcinoma and their Impact on the Inflammatory Tumor Microenvironment and Prognosis - Essakly, Ahlem (Transl Oncol, 2019)
Gene amplifications of PIK3CA or KRAS induce a downstream activation of the AKT-mTOR or RAF-ERK-pathways. Interactions of the active AKT pathway have been implicated in the inflammatory tumor microenvironment. Nothing is known about these interactions or prognostic power in esophageal adenocarcinoma (EAC). We retrospectively analyzed a large cohort of 685 EAC considering KRAS and PIK3CA gene amplification using fluorescence in situ hybridization (FISH) and immunohistochemistry. These results were correlated with clinical and molecular data as well as the inflammatory tumor microenvironment. Amplifications of KRAS were seen in 94 patients (17.1%), PIK3CA amplifications in 23 patients (5.0%). KRAS amplifications significantly correlated with nodal positive patients and poorer overall survival (OS) in the subgroup without neoadjuvant treatment (p = 0.004), coamplifications of Her2 (p = 0.027), and TP53 mutations (p = 0.016). PIK3CA amplifications significantly correlated with a high amount of tumor infiltrating T cells (p = 0.003) and showed a tendency to better OS (p = 0.068). A correlation with checkpoint makers (PD-L1, LAG3, VISTA, TIM3, IDO) could not be revealed. Our findings are the first to link the KRAS amplified genotype with lymphonodal positivity and poor prognosis and the PIK3CA-amplified genotype with a T cell–rich microenvironment in EAC. Future studies must show whether these two genotype subgroups can be therapeutically influenced. A dual inhibition of MEK and SHP2T could be effective in the subgroup of KRAS amplified EACs and an immune checkpoint blockade may prove to be particularly promising in the subgroup of PIK3CA-amplified EACs.